E+E- ANNIHILATION AT HIGH-ENERGIES AND SEARCH FOR THE T-QUARK CONTINUUM CONTRIBUTION - Brandelik, R; Braunschweig, W; Gather, K; Kadansky, V; Lubelsmeyer, K; Mattig, P; Martyn, H; Peise, G; Rimkus, J; Sander, H; Schmitz, D; Schultzvondratzig, A; et al. (Springer-Verlag, 1980)
Measurements of R, sphericity and thrust are presented for c.m. energies between 12 and 31.6 GeV. A possible contribution of a t Mathematical expression continuum can be ruled out for c.m. energies between 16 and 31 GeV. © 1980 Springer-Verlag.